PENGARUH PERILAKU EKONOMI PADA KETERGANTUNGAN JUDI ONLINE DI KALANGAN MAHASISWA - Fadhilla; Intan; Shafira; Aldi; Hafeyza (Transpublika Publisher, 2023)
This research aims to analyze the influence of economic behavior on online gambling addiction among students. The aim of this research is to provide insight into how economic factors influence student behavior in using online gambling or slots. This research uses a qualitative and quantitative approach with descriptive statistical data analysis techniques. Data was collected through interviews and questionnaires with 30 Tidar University students selected randomly based on their experience of having or currently playing online gambling. The results of this study show that the majority of respondents have high hopes for earning income from online gambling, even though they realize that the chance of losing is greater than the chance of winning. The majority of respondents believe that they have specific strategies that can increase their chances of winning. However, the results of this study show that individual involvement in playing online gambling can be financially detrimental for some respondents. This reflects the concept of economic behavior of individuals who are addicted to online gambling, where individuals are very biased in making decisions and are not objective, social factors that pressure the individual themselves and are attracted by the lure of profits that will be obtained if playing gambling games with the impression that the individual just play an ordinary game such as casino, poker, and others by betting a certain amount of money.